Enhancement of Photocatalytic Activity on TiO2-Nitrogen-Doped Carbon Nanotubes Nanocomposites - Lingling Wang; Long Shen; Yihuai Li; Luping Zhu; Jiaowen Shen; Lijun Wang (International Journal of Photoenergy)
TiO2-nitrogen-doped carbon nanotubes (TiO2-CNx) nanocomposites are successfully synthesized via a facile hydrothermal method. The prepared photocatalysts were systematically characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and thermogravimetric and differential scanning calorimetry analyses (TGA-DSC). The results show that the TiO2 nanoparticles with a narrow size of 7 nm are uniformly deposited on CNx. The photocatalytic activity of the nanocomposite was studied using methyl orange (MO) as a model organic pollutant. The experimental results revealed that the strong linkage between the CNx and TiO2 played a significant role in improving photocatalytic activity. However, the mechanical process for CNx and TiO2 mixtures showed lower activity than neat TiO2. Moreover, TiO2-CNx nanocomposites exhibit much higher photocatalytic activity than that of neat TiO2 and TiO2-CNTs nanocomposites. The improved photodegradation performances are attributed to the suppressed recombination of electrons and holes caused by the effective transfer of photogenerated electrons from TiO2 to CNx.